Critical analysis of the contribution of Peter Drucker to Administrative Science - Romero Gabancho, Elisbeth Dayana (2022)
The objective of this research was to analyze the great contributions provided by Peter Drucker throughout his career. With this purpose, the article focused on carrying out a bibliographical research, so that through a thorough search of the antecedents, a systematic and analytical review was carried out. Also, the research analyzed the implications or limitations of the topic in general and a proper confrontation was reached, based on the perspectives of the different authors. The results indicate that Drucker's contribution was multi-thematic and divergent at the time, since it covered many areas of administration such as management, innovation and marketing. In addition, it gave new points of view of the organizations and topics related to it, such as leadership, business knowledge and philosophy. In addition, the management model proposed by Drucker is based on actions to achieve executive effectiveness: practices, mission, spirit of performance, among others. In addition to current content such as innovation and marketing, topics developed in this article. In conclusion, the study emphasizes the different concepts most used in administration, giving importance to the leader over the manager since the former will be the one who significantly guides the other collaborators and provides them with the necessary knowledge to contribute to the achievement of the objectives organization goals.